Perancangan Interior Restoran dengan Penerapan Cerita Rakyat di Blitar dengan Konsep “Through the Time” - Vera Febriana Susilo; martino dwi nugroho; Poppy Firtatwentyna Nilasari (Intra, 2014)
Seeing the lack of dining facilities in the city of Blitar which is a city of tourism, and as well as its increasingly forgotten folklore that exist in this city then be made to the design of the restaurant with the application of folklore. The restaurant is applying folklore that exist in Blitar, it’s the origin of the town name of Blitar and Jaka Kandung and a Turtledove. Setting, character figures, and the atmosphere on the both story above was applied in the processing of space. The concept of design is through the time which applied folklore setting with the Majapahit era and combined with the current state showing design with eclectic style.